AB0345 Comparative Effectiveness of Biologic Agents for Patients with Rheumatoid Arthritis – Primary Analysis from The US Corrona Certain Study. (15th July 2016) - Pappas, D.A.; John, A.; Kremer, J.M.; Reed, G.W.; Sommers, T.; Greenberg, J.D.; Curtis, J.R.
Abstract : Background: Comparative effectiveness research (CER) can inform decisions regarding the choice of biologics for the treatment of RA. Objectives: To compare the efficacy of tumor necrosis factor inhibitors (TNFis) and non-TNFis (nTNFis) in real-world patients with RA previously treated with ≥1 TNFi. Methods: CERTAIN was a CER study nested within the US Corrona registry. 1 Adult patients with RA with moderate to high disease activity (CDAI >10) starting a TNFi or nTNFi (physician-driven choice of agent) were enrolled. For the primary analysis, only patients previously treated with ≥1 TNFi were included. The primary outcome was achievement of low disease activity (LDA) at 12 months (CDAI ≤10). A propensity score (PS) for the probability of treatment with a TNFi vs nTNFi was generated; patients outside the common area of support in the PS were excluded. Response rate was modeled using a mixed-effect logistic regression model with start of a biologic as the unit of analysis, adjusting for a priori and imbalanced baseline factors and to account for the clustering of patients within practice sites. As a sensitivity analysis, patients were matched 1:1 on the PS within each site. Results: Of the 2795 biologic starts captured, 1142 biologic naive and 562 nTNFi experienced were excluded, leaving 1091 biologic starts in 998 patients for analysis of response after a TNFi. After PS trimming, 1081 starts (566 [52.4%] nTNFi and 515 [47.6%] TNFi) remained. Patients who started nTNFis were significantly more likely to have longer disease duration, higher patient fatigue scores, Medicare insurance and more prior TNFi use. At 12 months, 29.4% of nTNFi and 24.3% of TNFi initiators were in LDA. In the adjusted analysis (Table), patients on nTNFis were significantly more likely to achieve LDA. However, when adjusting for site clustering, the results were no longer significant. Conclusions: In this large, real-world study, after ≥1 TNFi failure, switch to a nTNFi was favored over treatment with a subsequent TNFi, but was not statistically significant after adjusting for site clustering. Results warrant further study. References: Pappas DA, et al. BMC Musculoskeletal Disord. 2014;15:113. Acknowledgement: The Corrona CERTAIN study is sponsored by Corrona, LLC, with support from the AHRQ (R01HS018517). The majority of funding for CERTAIN was derived from Genentech, with additional support for substudies from Eli Lilly, Momenta Pharmaceuticals and Pfizer. CERTAIN investigators also receive support from the NIH [JRC AR053351, JDG AR054 412]. Disclosure of Interest: D. Pappas Employee of: Corrona, LLC, Paid instructor for: Novartis, A. John Employee of: Genentech, Inc, J. Kremer Shareholder of: Corrona, LLC, Consultant for: Abbvie, Amgen, BMS, Genentech, Lilly, Pfizer, Employee of: Corrona, LLC, G. Reed Employee of: Corrona, LLC, T. Sommers Employee of: Corrona, LLC, J. Greenberg Shareholder of: Corrona, LLC, Consultant for: AstraZeneca, Celgene, Genentech, Janssen, Novartis, Pfizer, Employee of: Corrona, LLC, J. Curtis Grant/research support from: Roche/Genentech, UCB, Janssen, Corrona, Amgen, Pfizer, BMS, Crescendo, AbbVie, Consultant for: Roche/Genentech, UCB, Janssen, Corrona, Amgen, Pfizer, BMS, Crescendo, Abb Vie